Cyrylometodejskie dziedzictwo piśmiennicze na Warmii i Mazurach - Jaroszewicz-Pieresławcew, Zoja (Acta Polono-Ruthenica, 2018)
It was the aim of the study to register and analyze manuscripts and prints written in the Cyrillic which have been collected in Warmia and Mazury. The article describes written monuments from the collections of libraries in Olsztyn: the library in Warmia and Mazury Seminary Hosianum (parchment leaves from the 14th century), University of Warmia and Mazury Library (manuscript Swiatcy from 1848), and Museum of Warmia and Mazury Library (two copies of the Lvov publication of the Altar Gospel Book from 1897), as well as the municipal and regional libraries (Monthly Menaion for October printed in Moscow in 1750) and a private collection (the Altar Gospel Book from 1815 printed in Poczajów. A volume of Służebnik (Wilno–Supraśl, 1692–1695) is in the possession of a Greek-Catholic parishioner from Giżycko. Additionally, volumes from the Old Believers’ monastery and Orthodox church in Wojnowo were described. Courtesy of their owners, the study is based also on manuscripts and prints which belong to the Old Believers from Ukta, Wojnowo, Ruciane-Nida and Piaski. The guardian of the Old Believers Monastery of Saviour and Holy Trinity allowed the author to photograph and describe the manuscripts and prints which have not been so far academically analysed. They are now stored in the Digital Library of the University of Warmia and Mazury thanks to a project financed by the National Science Centre. The described volumes, mainly liturgical in their character, served the needs of Christians in the east: Orthodox Christians, Old Believers and Greek-Catholics.